Combination of Botulinum Toxin and minocycline Ameliorates Neuropathic Pain Through Antioxidant Stress and Anti-Inflammation via Promoting SIRT1 Pathway - Zhi Yu; Jiayu Liu; Le Sun; Yusheng Wang; Hongmei Meng (Frontiers Media S.A., 2021)
Neuropathic pain (NP) is one of the intractable complications of spinal cord injury (SCI), with poor prognosis and seriously affects the quality of life of patients. This study aims to determine the treatment effect and mechanism of multimodal therapies in a rat model of SCI-induced NP by combining treatment with the anti-inflammatory agent minocycline (MC) and botulinum toxin (BoNT). The combined utilization alleviated SCI-induced NP and reduced apoptosis, inflammation, and oxidative stress of SCI by activating SIRT1 and dampening pAKT, P53, and p-NF-KB. BoNT with a concentration of 0.1 nm and MC with a concentration of 20 uM were selected for the experiment in the primary microglia and astrocytes treated with LPS. It was found that the combination of BoNT and MC obviously inhibits the inflammatory response and oxidative stress of glial cells, and notably activates SIRT1 and restrains pAKT, P53, and p-NF-KB. Therefore, in the treatment of SCI-induced NP, the combination of BoNT and MC markedly improves the therapeutic effect of NP by promoting the SIRT1 expression, thereby inactivating NF-KB, P53, and PI3K/AKT signaling pathway, inhibiting inflammation and oxidative stress as well as relieving SCI-induced NP.